Effect of Fiber Laser Irradiation on the Shear Bond Strength between Acrylic Resin and Titanium. (3rd September 2019) - Korkmaz, Fatih Mehmet; Aycan, Selin
Abstract : Objectives . The aim of this study is to investigate the shear bond strength of an acrylic resin to titanium after different surface treatment methods. Material and Methods . A total of seventy-two disc-shaped specimens (10 mm × 10 mm × 2 mm ) were prepared from titanium alloy. The specimens were randomly allocated to six equal groups: Group S (sandblasting), Group MP (metal primer), Group 10W (fiber laser 10 W), Group 20W (fiber laser 20 W), Group 10WMP (fiber laser 10 W+metal primer), and Group 20WMP (fiber laser 20 W+metal primer). All of the specimens were thermocycled up to 5000 cycles. After thermal cycling, a shear bond strength test was conducted. The shear bond strength data were analyzed with one-way ANOVA and Tukey's post hoc pairwise comparisons (p < 0.05 ). Results . While the highest values were determined in Group MP, the lowest values were observed in Group S. Additionally, Group MP exhibited significantly higher shear bond strength values than any of the other groups (p < 0.05 ) except Group 10WMP. Similar results were observed between Group MP and Group 10WMP (p > 0.05 ). The groups in which a metal primer was applied (Group MP, 10WMP, and 20WMP) showed significantly higher values than Group S. The shear bond strength values of Group 10W and Group 20W were similar. Conclusions . The application of a metal primer significantly improved the bond strength of acrylic resin to titanium. Fiber laser application may be an alternative method to sandblasting for improving the bond strength of acrylic resin to titanium.